The Influence of Using “THIEVES” Strategy on Junior High School Students’ Reading Comprehension - Islami, Yanda; Aisah, Siti; Sidik, Ezis Japar (Journal of English and Education (JEE), 2024)
Though reading in English is an imperative skill for students, teaching reading somehow still becomes a problem. This research aimed to investigate the influence of using the THIEVES (Title, Headings, Introduction, Every first sentence in a paragraph, Visuals and vocabulary, End-of-chapter questions, and Summary) strategy on reading comprehension among the eighth-grade students of a junior high school at Serang, Banten, Indonesia. This is a quasi-experimental study, specifically a non-equivalent control group design which aims to compare the outcomes between an experimental group (n= 33) that received the THIEVES Strategy intervention and  a control group (n= 34) that was not taught using the strategy. The results indicated a significant improvement in the experimental group’s reading comprehension scores compared to the control group. The result also leads to the rejection of the null hypothesis (H0) and accepting the alternative hypothesis (Ha) since the p-value shows Sig = .000 which means that the result is lower than .05. This experiment confirmed that THIEVES strategy has an influence on reading comprehension skills among students. The researchers then recommend English teachers to use an engaging and innovative strategy to captivate students’ interest and prevent boredom.